Preparation of high-performance microfiber synthetic leather base using thermoplastic polyurethane/sulfonated polysulfone electrospun nanofibers. Issue 14 (July 2019) - Zhao, Baobao; Qian, Xiaoming; Qian, Yao; Fan, Jintu; Feng, Yan; Duo, Yongchao; Zhang, Heng
Compared to natural leather, microfiber synthetic leather has many excellent qualities, such as chemical resistance and physical and mechanical properties. However, preparation of microfiber synthetic leather with a high water vapor transmission rate (WVT), moisture absorption and wearing comfort property is still a challenge. In this study, we prepared thermoplastic polyurethane (TPU)/sulfonated polysulfone (SPSf) electrospun nanofibers and applied them to a microfiber synthetic leather base (MSLB). The effects of TPU/SPSf nanofiber content on the structure and properties of the MSLB were investigated. The results indicated that the TPU/SPSf nanofibers with an average diameter of 0.12 µm were well distributed at all directions in the MSLB. Differential scanning calorimetry analysis showed four T g peaks, further demonstrating the existence of TPU/SPSf nanofibers. With the increase of TPU/SPSf nanofiber content from 0 to 30 wt%, the contact angles decreased gradually from 111.64° to 67.07°, leading to 55.19% improvement in the WVT value (from 2868.96 to 4452.24 g/(m 2 24 h)) and 26.25% improvement in the moisture absorption (from 628.70% to 793.75% mm/s). Simultaneously, when the nanofiber content was 30 wt%, the nanofibers tended to bundle and 6.79% decrement of air permeability was observed. Specifically, the softness of the MSLB was improved by 88.55%. Moreover, the thermal stability and the tear strength were also obviously enhanced. Consequently, this research provided a feasible and promising way to prepare a high-performance MSLB using TPU/SPSf nanofibers.